2017
DOI: 10.7863/ultra.16.06081
|View full text |Cite
|
Sign up to set email alerts
|

Enlarged Cavum Septi Pellucidi and Vergae in the Fetus: A Cause for Concern

Abstract: Our cohort had many associated clinical anomalies: 3 confirmed trisomy 21 and 1 probable trisomy 21, 2 genetic disorders, and 10 major adverse outcomes, 5 of which were grave. Although we studied a small cohort, we conclude that an enlarged cavum septi pellucidi or cavum vergae warrants consideration of genetic counseling, which may include noninvasive prenatal testing (cell-free DNA), amniocentesis with microarray testing, or both.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 39 publications
0
13
0
3
Order By: Relevance
“…Genetic abnormalities are found in only 1% of cases, but mutations in HESX1 , SOX1 , SOX2 (with severe eye defects and other anomalies), SOX3 , OTOX2 , and FGF8 have all been implicated . The significance of an enlarged (>10 mm) CSP is controversial, but it can be a sign of a CSP cyst and associated with other findings, including chromosomal abnormalities …”
Section: Common Prenatally Diagnosed Cns Defectsmentioning
confidence: 99%
“…Genetic abnormalities are found in only 1% of cases, but mutations in HESX1 , SOX1 , SOX2 (with severe eye defects and other anomalies), SOX3 , OTOX2 , and FGF8 have all been implicated . The significance of an enlarged (>10 mm) CSP is controversial, but it can be a sign of a CSP cyst and associated with other findings, including chromosomal abnormalities …”
Section: Common Prenatally Diagnosed Cns Defectsmentioning
confidence: 99%
“…A recent publication, however, has raised concern about 'prominent' (i.e. persistent and wide) septum pellucidum in young adults [16] and in foetuses [17].…”
Section: Discussionmentioning
confidence: 99%
“…Most published reports about the normal foetal CSPV to date are based on ultrasound and it is reported that the normal CSPV is robustly demonstrated on that modality. Ho et al [17] reviewed the recent literature and quote three papers [18][19][20] that report visualisation of CSPV in close to 100% of cases although the inability to visualise the associated anatomical structures (fornices and corpus callosum) consistently is well recognised. It is likely, on theoretical grounds, that iuMR imaging will improve definition of the CSPV and extend visualisation to include robust recognition of the fornices and corpus callosum.…”
Section: Discussionmentioning
confidence: 99%
“…Even when the CSP is present, its size and shape should be assessed for deviations from the norm. A CSP with a large width may indicate an increased risk of numeric or structural chromosomal abnormality . An abnormal ratio of the CSP length and width is considered to be an indirect sign of partial agenesis of the corpus callosum (pACC) .…”
Section: Introductionmentioning
confidence: 99%
“…A CSP with a large width may indicate an increased risk of numeric or structural chromosomal abnormality. [8][9][10] An abnormal ratio of the CSP length and width is considered to be an indirect sign of partial agenesis of the corpus callosum (pACC). 11,12 However, different studies have used different techniques and planes to measure the CSP.…”
Section: Introductionmentioning
confidence: 99%